Analisis Kandungan Logam Berat Timbal Dan Kadmium Pada Pengolahan Ikan Asin Di Kabupaten Banggai Kepulauan: Analysis of Heavy Metal Content of Lead (Pb) and Cadmium (Cd) In The Processing of Salted Fish In The Regency of Banggai Islands - Yonelian Yuyun; Andi Riesti Angelin Peuru; Nurlina Ibrahim (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2017)
This study was aimed to determine lead (Pb) and cadmium (Cd) contained in salted fish from Banggai Islands Regency. The sampleswere collected by purposive sampling from Tinangkung district, Liang district and South Totikum district. Pb and Cd content was measured using the atomic absorbtion spectrophotometry method. The results showed that layang salted fish from Tinangkung district had Pb content 0,0976 ± 0,0660 mg/kg and Cd content 0,0064 mg/kg. Lencam salted fish from Liang district had Pb content 0,2459 ± 0,0206 mg/kg and Cd content 0,0255 mg/kg. Cakalang salted fish from South Totikum district had Pb content 0,2100 ± 0,0148 mg/kg and Cd content 0,0254 mg/kg. Salt from Liang district had Pb content 0,3250 ± 0,0071 mg/kg and Cd content 0,1075 ± 0,0071 mg/kg. While the value of Pb and Cd in content salt from South Totikum district had 0,2250 ± 0,0071 mg/kg and 0,1025 ± 0,0035 mg/kg. From the result, could be concluded that salted fish and salt from three different places in Banggai Island Regency are still in limit to consume based on standart from Badan Standart Nasional Indonesia (BSNI) that determine 0,3 mg/kg for lead and 0,1 mg/kg for cadmium.